(N|WRIKA (B/s - (NsMIRNOW(B, (NaLEKSEJ wSEWOLODOWI^s ((NmOSKWA(B: s (NmOLODAQ GWARDIQs)
"(N|WRIKA(B" $1 (NSERIQ NAU^NO(B-(NPOPULQRNYH(B, (NNAU^NO(B-(NPUBLICISTI^ESKIH KNIG I ALXMANAHOW(B-(NEVEGODNIKOW(B, (NWYPUSKAW[IHSQ IZDATELXSTWOM (S0(NmOLODAQ GWARDIQ(S1 (NWO WTOROJ POLOWINE (BXX (NWEKA(B.s
rus
Keywords: (N|NCIKLOPEDIQs; (NbOTANIKAs